ANALISIS MANAJEMEN PELAYANAN HOTEL SARI INDAH DI KABUPATEN PROBOLINGGO - Retno, Riza Dwi (Universitas Panca Marga, 2023)
Public service is one of the important studies in the study of public administration. Hotel is a business sector engaged in services and one of the buildings that is rented out as a place for a short break for people who are traveling. The method used in this research uses a qualitative descriptive method using a case study approach. Data collection techniques through observation, interviews, and documentation. The focus in this study is to analyze hotel service management through the Service Triangle quality model, which has 3 indicators, namely service strategy, service system, and human resources. The results of the research that the researchers conducted were that the analysis of the service management of the Sari Indah hotel in Probolinggo Regency was sufficiently feasible for rural areas as evidenced by the existence of very strict regulations and this hotel building was also used as a place for Covid-19 isolation in 2021, apart from In the area around the hotel there are several other businesses, and many customers use the hotel's services. The three indicators, namely service strategy, service system, and human resources cannot be separated from one another. A manager has made one vision and mission as one of the company's strategies to achieve success. Customer satisfaction is the main goal in this business in the hospitality sector and with the hotel building it makes the area even more productive than before, such as reducing unemployment, many businesses in the culinary field, and there is a new building around the hotel, namely the Gending toll exit.